Applications of macroeconomic indicators in determining the predisposition to environmental threat - Milojević Ivan; Milanović Aleksandar (Održivi razvoj)
The research of ecological aspects in the macroeconomic trends of agricultural production occupies a significant place in improving the position of primary economic activities. Today, environmental air pollution is extremely significant primarily in the domain of livestock production and the emission of harmful substances into the air. In this paper, an attempt was made to present the macroeconomic indicators of agricultural production in ecological dimensions, using a comparative method. Investigation of comparative advantage through the RCA and LFI indices of the food processing industry and the intra-industry character of exchange measured by the GL index. refers to predispositions violation of ecological parameters.